Micro-Expressions of Fear During the 2016 Presidential Campaign Trail: Their Influence on Trait Perceptions of Donald Trump - Stewart, Patrick A.; Svetieva, Elena (Frontiers in Psychology, 2021)
The 2016 U.S. presidential election was exceptional for many reasons; most notably the extreme division between supporters of Donald Trump and Hillary Clinton. In an election that turned more upon the character traits of the candidates than their policy positions, there is reason to believe that the nonverbal performances of the candidates influenced attitudes toward the candidates. Two studies, before Election Day 2016, experimentally tested the influence of Trump's microexpressions of fear during his Republican National Convention nomination acceptance speech on how viewers evaluated his key leadership traits of competence and trustworthiness. Results from Study 1, conducted three weeks prior to the election, indicated generally positive effects of Trump’s fear microexpressions on his trait evaluations, particularly when viewers were first exposed to his opponent, Clinton. In contrast, Study 2, conducted four days before Election Day, suggests participants had at that point largely established their trait perceptions and were unaffected by the microexpressions.